Analyzing the effect of nanofiber orientation on membrane filtration properties with the progressive increase in its thickness: a numerical and experimental approach. Issue 1 (January 2020) - Akampumuza, Obed; Xu, Huilin; Xiong, Jian; Zhang, Hongnan; Quan, Zhenzhen; Qin, Xiaohong
One of the merits of modeling is that the computer-generated data is used in optimizing equipment and experimental designs, eliminating the costs associated with scaling up by experimentation. In this work, the filtration performance of nanofibers aligned diversely within virtual webs was numerically analyzed using Star CCM + and Ansys Fluent software. This knowledge was then used to fabricate two distinctly oriented nanofiber membranes via free surface electrospinning. Their filtration performance was studied by capillary flow porometry technology using POROLUX™ 100. The results of this were in agreement with the simulation work.